Domestic politics in Japan's free trade agreement (FTA) policy : the trans-pacific partnership (TPP) as case study - Chang, Entzu (2017)
It is widely acknowledged that an exploration of mass attitudes about trade is essential to the contemporary political economy of trade liberalization, and there are powerful empirical studies addressing this issue Two of the most famous trade theory models are developed to explain trade policy preferences of individuals and industries. However, despite with the existing literature and models, the puzzle with respect to how interest groups with different trade policy preferences interplay with each other and with governments, promoting or impeding the progress of FTA policy, is not solved. The dissertation attempts to provide analysis on the interactions between interest groups and the government when looking at Japan's FTA policy. We argue that Japan has constantly faced challenges from its domestic politics, particularly opposing camps, in promoting trade liberalization in its FTA policy. The dissertation particular examines the Trans-Pacific Partnership (TPP) to better examine the responses and reactions of Japanese interest groups to FTA policy.